Feasibility of precise and reliable glucose quantification in human whole blood samples by 1 tesla benchtop NMR. (2nd July 2020) - Stolz, Michael; Schlawne, Carolin; Hoffmann, Jens; Hartmann, Vanessa; Marini, Irene; Fritsche, Andreas; Peter, Andreas; Bakchoul, Tamam; Schick, Fritz
Abstract : The standard procedure for blood glucose measurements is enzymatic testing. This method is cheap, but requires small samples of open blood with direct contact to the test medium. In principle, NMR provides non‐contact analysis of body fluids, but high‐field spectrometers are expensive and cannot be easily utilized under clinical conditions. Low‐field NMR systems with permanent magnets are becoming increasingly smaller and more affordable. The studies presented here aim at exploring the capabilities of low‐field NMR for measuring glucose concentrations in whole blood. For this purpose, a modern 1 T benchtop NMR spectrometer was used. Challenges arise from broad spectral lines, the glucose peak locations close to the water signal, low SNR and the interference with signals from other blood components. Whole blood as a sample comprises even more boundary conditions: crucial for reliable results are avoiding the separation of plasma and cells by gravitation and reliable reference values. First, the accuracy of glucose levels measured by NMR was tested using aqueous glucose solutions and commercially available bovine plasma. Then, 117 blood samples from oral glucose tolerance testing were measured with minimal preparation by simple pulse‐acquire NMR experiments. The analysis itself is the key to achieve high precision, so several approaches were investigated: peak integration, orthogonal projection to latent structure analysis and support vector machine regression. Correlations between results from the NMR spectra and the routine laboratory automated analyzer revealed an RMSE of 7.90 mg/dL for the best model. 91.5% of the model output lies within the limits of the German Medical Association guidelines, which require the glucose measurement to be within 11% of the reference method. It is concluded that spectral quantification of glucose in whole blood samples by high‐quality NMR spectrometers operating at 1 T is feasible with sufficient accuracy. Abstract : Can reliable glucose quantification in whole blood be achieved by a modern 1 T low‐field benchtop NMR spectrometer? Possible applications are contactless measurements in extracorporeal systems or even in vivo. 117 oral glucose tolerance test blood samples were minimally prepared, measured by a simple NMR experiment and analyzed by integration, PLS and SVM regression. The best model achieved relatively high accuracy: 91.5% of the samples fulfilled the German Medical Association guidelines with an RMSE of 7.90 mg/dL.